Kepuasan Penumpang Terminal Antar Kota di Kabupaten Malinau Provinsi Kalimantan Utara - Welly Acang; M. Arif Hernawan; Deden Galih Ginanjar (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
The purpose of the study is to find out the effect of service quality of Malinau district inter-city terminal passengers’ satisfaction in North Kalimantan. The problems faced by the district were about the inadequate terminal’s condition, bad terminal’s management, naughty passengers who ride the bus from outside the terminal, the inadequate ticket box facility, and no integrated Standard Operating Procedures. To get the research subject, the writers were using Servqual analysis (gap), Importance Performance Analysis (IPA) with 30 Malinau inter-city terminal passengers as samples and Cartesius diagram. Based on the results, the writers find out that the terminal has not fulfilled the standard of the service quality which included the safety and security services, well-organized/reliable service, comfortable and convenience services, and the equality service.